3D graphene/hexagonal boron nitride composite nanomaterials synergistically reduce the friction and wear of Steel‐DLC contacts. Issue 4 (25th February 2021) - Qi, Shunshun; Wei, Xubing; Chen, Lin; Geng, Zhongrong; Luo, Jinqiong; Lu, Zhibin; Zhang, Guangan
Abstract: Green tribology is an engineering field, which is dedicated to reducing friction, wear and pollution to the environment. Diamond‐like carbon (DLC) films as coating is a very effective green friction material, but its friction of coefficient in the atmospheric environment still needs to be further reduced. Here, a common method for improving the tribological performance of DLC films in ambient atmosphere by adding 3D graphene/hexagonal boron nitride(h‐BN) composite nanomaterials as lubricant additive is proposed. By comparing with DLC film and other single additives, we can see that the 3D graphene/h‐BN composite nanomaterial as a lubricating additive reduce the friction coefficient and wear rate remarkably. By studying the tribological properties of the surface of the steel ball and DLC film, it is found that the friction protective film containing carbon, nitrogen and boron elements are formed on the surface. The presence of the friction layer can reduce friction efficiently, not only prevent the surface of the steel ball from being excessively worn, but also protect the DLC film from being damaged. The important thing is that it does not contain harmful elements and provides a new reference for the development of the next generation of oil‐free lubrication tribology. Accordingly, it is considered an environmentally friendly additive. Abstract : The tribological properties of 3D graphene, h‐BN and 3D graphene/h‐BN composite materials as steel‐DLC film contact lubricant additives are investigated in this paper. Lower friction and wear can be achieved when 3D graphene is mixed with h‐BN in a volume ratio of 1:1. This composite material has great application potential in various oil‐free lubrication fields.